The African Origins of Greek Philosophy: Ancient Egypt in Retrospect - Anakwue, Nicholas Chukwudike (Phronimon, 2018)
The demand of philosophising in Africa has faced a history of criticism that has been particularly Eurocentric and strongly biased. However, that trend is changing with the emergence of core philosophical thinking in Africa. This paper is an attempt to articulate a singular issue in this evolution—the originality of African philosophy, through Ancient Egypt and its influence on Greek philosophy. The paper sets about this task by first exposing the historical debate on the early beginnings of the philosophical enterprise, with a view to establishing the possibility of philosophical influences in Africa. It then goes ahead to posit the three hypotheses that link Greek philosophy to have developed from the cultural materiality of Ancient Egypt, and the Eurocentric travesty of history in recognising influences of philosophy as from Europe alone, apart from Egypt.